Case Study of Leadership Practices and School-Community Interrelationships in High-Performing, High-Poverty, Rural California High Schools - Marcia Masumoto; Sharon Brown-Welly (Journal of Research in Rural Education, 2009)
Many rural California high schools are impacted by the disadvantages of poverty, non-English speaking students, limited resources, changing demographics, and challenges of the rural context. Focusing on contemporary leadership theories and school-community interrelationships, this qualitative study examines the practices of educational leaders in three highperforming, high-poverty, rural California high schools. The authors employed case study methodology using a variety of data sources including document analysis, interviews, and observations. Cross-case findings revealed that the local educational leadership had effectively employed multiple instructional, distributed, and transformational practices to improve student outcomes, and had established multiple formal and informal linkages with institutional entities outside of the school to accomplish their missions. Contributors to school-wide success in each case included: focus on instruction, standards, and expectations; strengths of teachers, and; development of multiple support systems for students with varying needs. Educational leaders in the schools studied with the highest poverty rates and highest percentages of English Language Learners made significant improvements in student achievement through active involvement of parents and the mobilization of other external and community resources.